2020
DOI: 10.3389/fneur.2020.00903
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Sphingo- and Glycerophospholipid Impairment to Select Effective Drugs and Biomarkers for CMT1A

Abstract: In Charcot–Marie–Tooth type 1A (CMT1A), Schwann cells exhibit a preponderant transcriptional deficiency of genes involved in lipid biosynthesis. This perturbed lipid metabolism affects the peripheral nerve physiology and the structure of peripheral myelin. Nevertheless, the identification and functional characterization of the lipid species mainly responsible for CMT1A myelin impairment currently lack. This is critical in the pathogenesis of the neuropathy since lipids are many and complex molecules which play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 98 publications
(131 reference statements)
2
15
0
Order By: Relevance
“…Consequently, droplet formation in glia may be an early marker for neurodegeneration. Additionally, while the dynamics of TAG accumulation have not been fully characterized in peripheral nerves, increases in TAG species have been associated with several neuropathies including CMT2, HSN1, CMT1E, and CMT1A (Marshall et al, 2014;Zhou et al, 2019;Giudetti et al, 2020;Visigalli et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, droplet formation in glia may be an early marker for neurodegeneration. Additionally, while the dynamics of TAG accumulation have not been fully characterized in peripheral nerves, increases in TAG species have been associated with several neuropathies including CMT2, HSN1, CMT1E, and CMT1A (Marshall et al, 2014;Zhou et al, 2019;Giudetti et al, 2020;Visigalli et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As previously noted in this work, diabetes is the known progenitor of diabetic neuropathy, but only 20-40% of patients with diabetes acquire diabetic neuropathy and both the severity and form of the disease vary greatly in those individuals (M C Perez-Matos, . Additionally, patients with the most common form of CMT, CMT1A, resulting from nearly identical duplications of a chromosomal segment containing the gene encoding peripheral myelin protein 22 (PMP22), have greatly varied phenotypic presentation and progression (Visigalli et al, 2020). This variation suggests that unknown factors, either environmental or genetic, act as modulators in these disorders.…”
Section: Implications In Other Disease Pathologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Diet supplementation with phosphatidylcholine and phosphatidylethanolamine improved myelin biosynthesis and nerve function in this model [ 67 ]. The lipids supplementation approach is further supported by a recent study showing impairments of sphingolipid and glycerophospholipid metabolism in CMT1A [ 118 ]. Although clinical trials showed no side-effects under this treatment [ 68 ], it remains unknown whether high doses of dietary phospholipids can benefit CMT1A patients.…”
Section: Emerging Treatments For Demyelinating Cmt Neuropathiesmentioning
confidence: 98%
“…10 Studies using a rat model of CMT1A have reported that Schwann cells in this disease exhibit reduced transcription of the genes required for myelin lipid biosynthesis. [11][12][13][14] This perturbed lipid metabolism could be involved in the pathogenesis of the disease by reducing lipid incorporation into myelin, which produces structural changes in the myelin sheath. 11 Moreover, a lipid-enriched diet has been shown to improve myelination in CMT animal models, 11,13 which suggests that exogenous lipid delivery to the peripheral nerves via plasma could potentially affect the myelination of nerve bers in this disease.…”
Section: Introductionmentioning
confidence: 99%